The prevalence and epidemiology of genetic renal disease amongst adults with chronic kidney disease in Australia - Mallett, Andrew (BioMed Central, 2014)
BACKGROUND: There are an established and growing number of Mendelian genetic causes for chronic kidney disease (CKD) in adults, though estimates of prevalence have been speculative. The CKD Queensland (CKD.QLD) registry enables partial clarification of this through the study of adults with CKD receiving nephrology care throughout Queensland, Australia. METHODS: Data from the first 2,935 patients consented to the CKD.QLD registry across five sites was analysed, with a comparison between those with and without Genetic Renal Disease (GRD). Prevalence of GRD amongst those with diagnosed CKD, the general population, and commencing renal replacement therapy (RRT) was calculated using the CKD.QLD registry, national census data and extracted Australian and New Zealand Dialysis and Transplantation (ANZDATA) registry report data respectively. RESULTS: Patients with GRD constituted 9.8% of this Australian adult CKD cohort (287/2935). This was lower than in local incident RRT cohorts (2006–2011: 9.8% vs 11.3%, x(2) = 0.014). Cases of adult CKD GRD were more likely to be female (54.0% vs 45.6%; x(2) = 0.007), younger (mean 52.6 yrs vs 69.3 yrs, p < 0.001), have a higher eGFR (mean 49.7 ml/min/1.73 m2 vs 40.4 ml/min/1.73 m2, p < 0.001), and have earlier stage renal disease (CKD Stage 1: 15.7% vs 5.1%, x(2) < 0.0005) than those without GRD. CONCLUSIONS: The proportion of GRD amongst an Australian adult CKD population in specialty renal practice is similar to past estimations. GRD is a significant cause for CKD and for RRT commencement, presenting opportunities for ongoing longitudinal study, directed therapeutics and clinical service redesign.